Test–retest reliability of EEG spectra during a working memory task - Näpflin, Markus; Wildi, Marc; Sarnthein, Johannes (NeuroImage (Orlando, Fla.), 2008)
The inter-individual variation of EEG spectra is large even for the same cognitive task. We asked whether task-induced EEG spectra remain stable over more than a year. We recorded EEG in 41 healthy adults who performed a modified Sternberg task. In 20 subjects EEG was recorded in a second session with retest intervals 12–40 months. For electrodes AFz, Cz and Pz peak frequency and peak height were determined. We compared the curve shape of power spectra by regressing spectra pairwise onto each other and calculated a t-value. The t-value and pairwise differences in peak frequency and peak height between all sessions were entered into a generalized linear model (GLM) where binary output represents the recognition probability. The results were cross-validated by out-of-sample testing. Of the 40 sessions, 35 were correctly matched. The shape of power spectra contributed most to recognition. Out of all 2400 pairwise comparisons 99.3% were correct, with sensitivity 87.5% and specificity 99.5%. The intra-individual stability is high compared to the inter-individual variation. Thus, interleaved EEG-fMRI measurements are valid. Furthermore, longitudinal effects on cognitive EEG can be judged against the intra-individual variability in subjects.